The interleukin-6 promoter -597/-572/-174 genotype does not affect interleukin-6 production in hemodialysis patients - Schulte, Friederike Barbara; Schnülle, Peter; Bugert, Peter; Klüter, Harald; Müller-Steinhardt, Michael (Journal of interferon & cytokine research, 2011)
Kidney transplant recipients with the interleukin-6 (IL-6) GGG/GGG promoter −597/−572/−174genotype were shown to have a better long-term outcome. Further, the same −597/−572/−174genotype was found to be associated with less IL-6 production in healthy control subjects. To verify this observation in potential kidney transplant recipients, IL-6 production was analyzed in 85/142 hemodialysis patients. We could not confirm an impaired IL-6 secretion in carriers of the GGG/GGG −597/−572/−174genotype and propose a significantly lower IL-6 production in hemodialysis patients versus healthy control subjects to explain this. However, we suggest subsequent studies of IL-6 production in kidney allograft recipients to further elucidate the pathophysiological relevance of IL-6 for transplant outcome.
Die Ziffern -597/-572/-174 sind im Titel hochgestellt
Gesehen am 27.10.2022